Pérez Prado: A Story of Rhythm, Drumming and Dancing. (1st July 2021) - Fernández, Raúl
Abstract : Despite his success or perhaps because of it, the renowned Cuban musician pérez prado was the target of criticism from some of his contemporaries. For some jazz musicians prado's compositions lacked substance, were commercial even bordering on corny. Yet he also composed "concerts" which hardly had commercial success as an object. If his mambos are judged as lacking in quality, how to explain the interest classical musicians expressed in them? These questions led me to consider an idea advanced in popular music circles as to whether there was not one but several "pérez prados", i.e. one that composed mambos; another dedicated to marketing light commercial tunes; yet a third focused on "serious" concert music. An analysis of three central elements in all of his work do not reveal several "pérez prados". Rather it demonstrates that prado was a single composer with different facets arising from diverse circumstances and artistic and economic needs, but based on the same musical foundations. prado was a maestro whose variations never abandoned the main themes: rhythm, drums and dancing.